TGFβ Signaling Increases Net Acid Extrusion, Proliferation and Invasion in Panc-1 Pancreatic Cancer Cells: SMAD4 Dependence and Link to Merlin/NF2 Signaling - Malinda, Raj R.; Zeeberg, Katrine; Sharku, Patricia C.; Ludwig, Mette Q.; Pedersen, Lotte B.; Christensen, Søren T.; Pedersen, Stine F. (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is a major cause of cancer-related death, with a 5-year survival of less than 10% and severely limited treatment options. PDAC hallmarks include profound metabolic acid production and aggressive local proliferation and invasiveness. This phenotype is supported by upregulated net acid extrusion and epithelial-to-mesenchymal transition (EMT), the latter typically induced by aberrant transforming growth factor-β (TGFβ) signaling. It is, however, unknown whether TGFβ-induced EMT and upregulation of acid extrusion are causally related. Here, we show that mRNA and protein expression of the net acid extruding transporters Na+/H+ exchanger 1 (NHE1, SLC9A1) and Na+,HCO3- cotransporter 1 (NBCn1, SLC4A7) are increased in a panel of human PDAC cell lines compared to immortalized human pancreatic ductal epithelial (HPDE) cells. Treatment of Panc-1 cells (which express SMAD4, required for canonical TGFβ signaling) with TGFβ-1 for 48 h elicited classical EMT with down- and upregulation of epithelial and mesenchymal markers, respectively, in a manner inhibited by SMAD4 knockdown. Accordingly, less pronounced EMT was induced in BxPC-3 cells, which do not express SMAD4. TGFβ-1 treatment elicited a SMAD4-dependent increase in NHE1 expression, and a smaller, SMAD4-independent increase in NBCn1 in Panc-1 cells. Consistent with this, TGFβ-1 treatment led to elevated intracellular pH and increased net acid extrusion capacity in Panc-1 cells, but not in BxPC-3 cells, in an NHE1-dependent manner. Proliferation was increased in Panc-1 cells and decreased in BxPC-3 cells, upon TGFβ-1 treatment, and this, as well as EMT per se, was unaffected by NHE1- or NBCn1 inhibition. TGFβ-1-induced EMT was associated with a four-fold increase in Panc-1 cell invasiveness, which further increased ~10-fold upon knockdown of the tumor suppressor Merlin (Neurofibromatosis type 2). Knockdown of NHE1 or NBCn1 abolished Merlin-induced invasiveness, but not that induced by TGFβ-1 alone. In conclusion, NHE1 and NBCn1 expression and NHE-dependent acid extrusion are upregulated during TGFβ-1-induced EMT of Panc-1 cells. NHE1 upregulation is SMAD4-dependent, and SMAD4-deficient BxPC-3 cells show no change in pHi regulation. NHE1 and NBCn1 are not required for EMT per se or EMT-associated proliferation changes, but are essential for the potentiation of invasiveness induced by Merlin knockdown.